Calcite-dissolving bacteria: promising approach as bio-fertilizer - Hambo, Christina Lemson; Shitindi, Mawazo Jamson; Sibuga, Kalunde Pilly; Nzogela, Yasinta Beda (Frontiers in Microbiology, 2025)
Calcium (Ca) is an essential macronutrient and a secondary messenger for the proper growth and functioning of plants. It is essential for membrane stability, cell integrity, cell division, and elongation. In the soils, Ca exists in inorganic and organic forms. Inorganic fraction constitutes soil-Ca solution, which is readily available for plant uptake, exchangeable Ca, which replenishes the solution pool, and fixed Ca, which replenishes exchangeable Ca slowly upon weathering to release calcium ion (Ca2+). Similarly, organic forms of Ca are inactive and unavailable for plant uptake until decomposed, mineralized, and dissolved into Ca2+. Calcium deficiency in soil reduces plant growth, development, and yields, which can be rectified by applying Ca fertilizers and Ca-rich soil amendments. Unfortunately, many smallholder farmers have limited access to Ca fertilizers, and thus cannot purchase optimal amounts required for enhancing plant growth and crop yields. This calls for alternative technologies that enhance the dissolution of unavailable forms of Ca in the soil. Calcite-dissolving bacteria (CDB) are a functional group that can dissolve poorly soluble calcite minerals into Ca2+, thus increasing the % Ca2+ saturation on the soil exchange sites, making it available for plant uptake. CDB offers an economically viable and environmentally friendly option to overcome Ca deficiency in the soil. CDB has been a subject of research interest, especially in its ability to precipitate calcite for soil stabilization and strength enhancement. However, studies on using CDB to improve the Ca2+ supply power of the soils and their resultant effects on plant growth and crop productivity, especially under field conditions, are limited. For effective formulation of CDB-based biofertilizers, one should understand the chemistry of calcite, Ca availability in the soil, diversity of CDB, mechanisms of calcite dissolution by CDB, mechanisms by which CDB promote plant growth, and the potential of CDB as biofertilizers in crop production. This review is among the first to provide detailed information on these aspects of CDB. We employed a Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method to explore and expand the understanding of the potential of CDB as biofertilizers in crop production.